Involvement of Farm Women in Decision making Regarding Dairy Farming in Junagadh District of Gujarat State - Patel, S. J.; Kumar, R.; Patel, A. S.; Patel, N. R.; Parmar, V. N. (Indian Journal of Hill Farming, 2017)
India is an agriculture based country and livestock sector is an integral component. Women play crucial and significant role in livestock rearing, all spheres of economic life and contribute richly towards national income. A survey study was conducted to acquire the first hand information on Personal and socio-economic characteristics and Decision making of farm women regarding dairy farming and also correlation between these two variables studied in Junagadh district of Gujarat state, India. A simple random sampling technique was used in the selection of dairy farm women. The total sample constitutes 200 dairy farm women, four talukas and five village from each taluka. Total ten (10) respondents selected from each village of the district. The data were collected by personal interview technique through a structural schedule. In Personal and socio-economic characteristics, majority (73.50 %) of the farm women belonged to middle age group, 31 per cent of the farm women were educated up to primary level of education. Majority (44 %) of the dairy farm women were from SEBC caste category, majority (72 %) of the farm women belonged to low level of income (<150000 rupees) group, majority (68.50 %) and (41.50 %) of the farm women belonged to the joint type and large size of families, respectively. Majority (53.50 %) of the farm women respondents were with Marginal land holding i.e. up to 1.00 hectare. Great majority (94.50 %) of farm women had major occupation of animal husbandry along with agriculture. Nearly half of the respondents (47 %) had low social participation, Majority (65.50 %) of the farm women were found with medium experience in dairy farming. Majority (75.50 %) of the farm women used medium sources of information for obtaining information about dairy farming and Majority (57.50 %) of the farm women had medium sized milch animals. In Decision making of farm women regarding dairy farming include majority (80.57 % and 80.11 %) of farm women involved in decision making about milking and preparation of milk products and management of milch animals, respectively. Majority (72.97 % and 68 %) of the farm women involved in decision making regarding breeding practices and feeding practices, respectively. Majority (64.12 %) of farm women involved in decision making regarding health care practices of milch animals. Majority (55.94 %) of the farm women involved in decision making regarding general aspects in dairy farming.